Bioelectrical Insight: Correlation Cell Count and Electrical Impedance of Whole Blood throughout Storage with an Impedance Analyzer Methode - Aini, Viranita Qurotul; Widodo, Chomsin S.; Retnaningtyas, Ekowati (Postgraduate, University of Mataram, 2024)
Blood, a vital tissue comprising blood cells within the plasma matrix, plays a crucial role in transporting oxygen, nutrients, and functional components throughout the body. Insufficient blood levels can lead to disorders or life-threatening conditions, necessitating blood transfusions for those experiencing deficiencies. Blood banks store blood products to meet transfusion needs, emphasizing safety, donor health, patient conditions, cross-matching accuracy, and storage quality. Examining stored blood indicates an individual's physiological response to environmental changes, with quantitative and qualitative changes visible through whole blood cell count and impedance parameters. Electrical impedance spectroscopy, which measures these biological properties, shows that although blood cell count remains stable over 35 days, impedance characteristics change significantly. Analysis of the Nyquist Zriil plot reveals a consistent decrease in Zriil values, indicating reduced extracellular resistance (Res) over time. These impedance changes reflect alterations in blood morphology, providing crucial insights into the quality of stored blood. In conclusion, electrical impedance spectroscopy effectively monitors stored blood quality, detecting significant changes in extracellular resistance over extended storage periods. These findings underscore the importance of regular monitoring and proper management of stored blood to ensure its safety and effectiveness for transfusions.